Analysis of Water Quality in Batujai Reservoir Due to Community and Business Activities in Central Lombok Regency - SUPARDIONO, Supardiono; ARTHANA, Wayan; ADNYANA, Wayan Sandi; SUYASA, Wayan Budiarsa; SUDIPA, Nyoman (Journal of Environmental Management and Tourism; Vol 12 No 1 (2021): JEMT 1(49) Spring 2021, 2021)
The development of an area must be accompanied by an ever-increasing population growth which will also increase the waste produced. Waste production will put pressure on the environment if it is not managed properly which will eventually end up in water bodies. The increased pollution load is also caused by the habit of people disposing of domestic waste, both liquid waste and solid waste directly into the water. Batujai Reservoir is one of the vital objects for the survival of the people of Central Lombok in particular, and the people of Lombok Island in general. Because of its vital role, the Batujai Reservoir needs to be saved so that the reservoir ecosystem can carry out its functions and benefits in improving the welfare of the people of Central Lombok. There are several community activities that are a source of direct reservoir water pollution (point source) such as fishing activities using floating net cages and disposal of domestic waste by the community which is directly channeled to water bodies. Pollutants collected in the Batujai Reservoir will reduce the water quality of the Batujai Reservoir. This research aims to analyze the water quality of the Batujai Reservoir which is caused by business activities and the community based on Government Regulation Number 82 of 2001 and to determine the water pollution index of the Batujai Reservoir. This study uses a quantitative approach by collecting primary data from direct observations in the field and secondary data based on previous research reports and government reports. The results showed that the average physical parameters were above the water quality standard threshold for class II water quality, the average chemical parameters were above the water quality standard for class III and class IV water quality, while the biological parameters were above the threshold. Water quality limits for class II and class III. The decline in water quality in the Batujai Reservoir is caused by various wastes entering the Batujai Reservoir water bodies. The analysis result with storet system shows that the water quality of Batujai Reservoir is in bad condition or heavily polluted.